Design of photovoltaic system for public school building - Muhammad Abdillah; Fathan Mujahid Satria; Nita Indriani Pertiwi; Herlambang Setiadi (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The increase in energy needs to support sustainable development will trigger a large additional power supply. Unfortunately, a current energy source is mostly produced by fossil fuels. This condition can affect the increase of global warming and climate change. Nowadays, many countries including Indonesia are aware of the effect of the use of fossil fuels on environmental devastation. Therefore, the use of clean energy gets more attention from many countries since its energy source is unlimited and harvested from nature. One of the clean energy sources that are widely utilized over the world is photovoltaic (PV). PV is an appropriate clean energy technology to be utilized in Indonesia since this country lies on the equator line and gets solar irradiance over the year. This paper proposed the design of PV systems for a public-school building. These PV schemes proposed in this study are classified into off-grid, on-grid, and hybrid PV systems. From the simulation results, it is shown that the hybrid PV system with energy supplied by PT. PLN (State Electricity Company) results in the highest saving annual cost and provides an environmentally friendly energy source for public-school buildings.